The Use of Quranic Learning Strategies Through the Wafa Method in Elementary Schools - Demina Demina; Tachioka Rexy; Asuncion Danyl (Journal International Inspire Education Technology, 2022)
The learning strategy of the Qur’an in Indonesia is very influential in human life, especially students who are about to start education in religious matters. In this case, researchers found a solution by teaching the Qur’an starting from elementary school. To achieve the success of the learning process, it is necessary to use qur’anic learning strategies through effective learning methods, such as the Wafa Method with the aim of making it easier for students or students / students to be able to read the Qur’an easily, so that what they read can also be remembered and memorized and also trained in Arabic writing. The Wafa Method is a right-brain method in learning using multisensory aspects or a combination of different senses, such as visual, auditory, and kinesthetic. This research uses a descriptive method with a qualitative approach. The results of this study can be concluded that the implementation and evaluation of the Wafa method in the Quranic learning strategy is quite good. however, in the learning process, students or students / students are asked to be more focused. So we can conclude that this wafa method is very suitable for use in the implementation of learning strategies for achieving the memorization of the Qur’an quickly with understanding. To achieve learning, it is carried out every Monday-Friday so that the memorization of students every day will increase in number and also be able to make students become memorizers of the Qur’an.